Isolation and molecular characterization of the FLOWERING LOCUS C gene promoter sequence in radish (Raphanus sativus L.) - Yuan-yuan XU; Jing WANG; Shan-shan NIE; Dan-qiong HUANG; Yan WANG; Liang XU; Rong-hua WANG; Xiao-bo LUO; Li-wang LIU (Journal of Integrative Agriculture, 2016)
Both bolting and flowering times influence taproot and seed production in radish. FLOWERING LOCUS C (FLC) plays a key role in plant flowering by functioning as a repressor. Two genomic DNA sequences, a 3 046-bp from an early- and a 2 959-bp from a late-bolting radish line were isolated and named as RsFLC1 and RsFLC2, respectively, for they share approximately 87.03% sequence identity to the FLC cDNA sequences. The genomic DNA sequences, 1 466-bp and 1 744-bp, flanking the 5′-regions of RsFLC1 and RsFLC2, respectively, were characterized. Since both of them harbor the basic promoter elements, the TATA box and CAAT box, they were designated as PRsFLC1 and PRsFLC2. The transcription start site (TSS) was identified at 424 and 336 bp upstream of the start codon in PRsFLC1 and PRsFLC2, respectively. cis-regulatory elements including CGTCA (MeJA-responsive) and ABRE (abscisic acid-responsive) motifs were found in both promoters, while some cis-regulatory elements including TCA element and GARE-motif were present only in PRsFLC1. These sequence differences lead to the diversity of promoter core elements, which could partially result in the difference of bolting and flowering time in radish line NauDY13 (early-bolting) and Naulu127 (late-bolting). Furthermore, to investigate the activity of these promoters, a series of 5′-deletion fragment-GUS fusions were constructed and transformed into tobacco. GUS activity was detected in PRsFLC1-(1 to 4)-GUS-PS1aG-3 and PRsFLC2-(1 to 4)-GUS-PS1aG-3 transgenic tobacco leaf discs, and this activity progressively decreased from PRsFLC-1-GUS-PS1aG-3 to PRsFLC-5-GUS-PS1aG-3. Deletion analysis indicated that the cis-regulatory elements located at −395 bp to +1 bp may be critical for specifying RsFLC gene transcription.